Modeling with Macro-Financial Linkages : Credit and Policy Shocks in Emerging Markets - Benes, Jaromir (IMF Working Papers; Working Paper, 2009)
This paper develops a stylized, small, open economy macro model that incorporates an explicit and non-trivial role for financial intermediation. It illustrates how such a model could be used for policy analysis in an emerging market economy where policymakers are concerned about risks associated with rapid credit growth, financial dollarization, and foreign borrowing, while lacking traditional tools to effect monetary policy transmission, and hence could resort to more direct instruments, such as foreign exchange market intervention and regulatory and administrative measures. Calibrating the model to a stylized emerging European economy, the paper simulates real and financial sector implications of various external and policy-related shocks that could be used as input for monetary policy making.